The Relationship Between Family Social Support and Nurse Anxiety Level in the COVID-19 Isolation Room at Klungkung Regency Hospital - Juliastiti Rahayu, Ni Made; Nuryanto, Kadek; Rismawan, Made (CV. Dyoqu Publishing Management, 2025)
Background: Nurses are at the forefront of handling COVID-19 patients, who have a high risk of experiencing psychological pressure in the form of anxiety. Social support from family is considered as one of the protective factors that can reduce anxiety, but its effectiveness in the context of caring for COVID-19 patients still needs further research. Aims: This study aims to determine the relationship between family social support and the anxiety level of nurses assigned to the COVID-19 isolation room at Klungkung Regency Hospital. Methods: This study used a quantitative approach with a correlative descriptive design and cross-sectional design. The sampling technique used total sampling with a total of 62 respondents. Data were collected through two questionnaire instruments: family social support questionnaire (20 items) and Zung Self-Rating Anxiety Scale (SAS). Data analysis was conducted using the Spearman-rho test. Result: Most respondents (90.3%) had a high level of family social support and did not experience anxiety (96.8%). However, the statistical test results showed that there was no significant relationship between family social support and nurses' anxiety level (p = 0.123). Conclusion: This study concludes that family social support does not have a significant relationship with the anxiety level of nurses in the COVID-19 isolation room. Therefore, more attention is needed from institutions and the work environment in providing comprehensive psychological support for health workers.